“Desarrollo de un SCADA de un entorno virtual de flujo y monitoreo remoto en tiempo real basado en una arquitectura IOT” - Tipan Tuitise, Alex Patricio (2020)
The present degree work was carried out with the purpose of developing a SCADA of a virtual environment of flow and remote monitoring in real time based on an IoT architecture, by means of the use of the virtual instrumentation and simulation software, it is conformed of the following stages; design of the industrial process, communication with the programming software, development of the SCAD and shipment of data an industrial cloud. The design of the virtual flow process considered the flow control and production output processes, which were replicated in the industrial simulation software. Software that performs 3D simulation, communication with industrial devices such as PLC and control in real time. The module in charge of carrying out the flow control and production output is the PLC SIM, which is an advanced virtual simulation software of programmable logic controllers, which aims to check their operation, and also allows simulations of the TIA PORTAL program without the need for hardware. The SCADA was performed in the Ignition software, which allows communication with programmable logic controller through the ethernet TCP/IP protocol and for the IOT it was performed through program blocks that are added to the controller programming in the TIA PORTAL. The result is a low-cost SCADA that allows data acquisition, real time manipulation and visualization of variables through an industrial cloud. With the development of this project, it is intended to improve the monitoring in the processes of flow control and production output through the supervision of the most dispensable variables of the processes, remote control, sending of alarms and data acquisition in a web platform